Dielectric properties and phase transition behaviors in (1-x) PbZrO3 -xPb (Mg1/2 W1/2) O3 ceramics - Vittayakorn, Naratip; Charoonsuk, Piyanut; Kasiansin, Panisara; Wirunchit, Supamas; Boonchom, Banjong (My University, 2009)
The solid solution of lead zirconate [PbZrO3 (PZ)] and lead magnesium tungstate [Pb (Mg1/2 W1/2) O3 (PMW)] has been synthesized by the wolframite precursor method. The crystal structure, phase transformations, dielectric and thermal properties of (1-x) PZ-xPMW, where x=0.00-0.10, were investigated. The crystal structure of sintered ceramics was analyzed by x-ray diffraction. Phase-pure perovskite was obtained for all compositions. Furthermore, a change from orthorhombic to rhombohedral symmetry was observed as the mole fraction of increased PMW. As a result, it was found that PbZrO 3 -Pb (Mg1/2 W1/2) O3 undergoes successive transitions from the antiferroelectric phase to the ferroelectric phase to the paraelectric state. The coexistence of orthorhombic and rhombohedral phases in this binary system is located near the composition x=0.1. © 2009 American Institute of Physics.